A Primer on the Financial Policies of Chinese Firms: A Multi‐country Comparison. Issue 4 (December 2016) - Zenner, Marc; McInnes, Peter; Chivukula, Ram; Le, Phu
Abstract : Chinese companies have grown rapidly over the past few decades, and become increasingly global in the process. In the past five years, the aggregate market capitalization of public companies in China increased more than ten‐fold and their revenue from outside China grew 60%. Nevertheless, Chinese companies have financial policies that are notably different from those of their global counterparts in North America and Europe, and that difference could end up limiting their future profitability and growth. In this report, J.P. Morgan's Corporate Finance Advisory team compares the capital structures of large Chinese companies to those of the largest companies in the U.S., the U.K. and Germany. Among the most important findings, Chinese companies have materially more leverage, much greater reliance on bank loans than bonds, and maturities that are almost 80% shorter than those of typical U.S. companies. To bring their balance sheets in line with those of their global peers, Chinese companies are likely to have to raise over 5 trillion yuan (over $750 billion) in equity while also issuing roughly the same amount in bonds. At the same time, in order to attract that capital on economic terms, they will likely need to find ways to increase the profitability of their businesses, whose return on equity is well below international standards. As the authors point out in closing, making such significant changes in financial and operating policies could be challenging for all stakeholders, and cause some potential dislocation in the short run. But however disruptive, such changes are most likely to ensure the ability of Chinese companies to create the most value in the long run.